Discrepancies between Perception and Reality of Tobacco Use in Bangladesh: Psychological Disorders, Mental Illness, and Suicidal Risks - Hsiao-Ling Huang; Ashek Elahi Noor (Liaquat National Journal of Primary Care)
Tobacco consumption, in both smoking and smokeless forms, remains a significant public health concern in Bangladesh. However, there is a striking discrepancy between public perception and the actual impact of tobacco use, particularly regarding its psychological consequences. This study employs a mixed-methods approach, combining survey data from 5,000 respondents across urban and rural Bangladesh with a comparative analysis of global tobacco-related health outcomes. The results indicate that 42.6% of Bangladeshis use tobacco, with 20.6% consuming smoking tobacco (e.g., cigarettes, bidis) and 22% using smokeless tobacco (e.g., jarda, gul, sada pata). Despite widespread awareness of tobacco’s physical health risks—such as lung cancer and cardiovascular diseases— only 38% of respondents recognize its significant impact on mental health, particularly depression, anxiety, and suicidal ideation. Statistical analysis reveals that smokeless tobacco users in Bangladesh exhibit a 3.2 times higher risk of developing psychological disorders compared to non-users. Unlike smoking, smokeless tobacco contains unregulated levels of carcinogenic nitrosamines and heavy metals, leading to an increased risk of oral cancer, neurotoxicity, and heightened dependency. Cross-national comparisons show that while countries like Sweden and the U.S. have successfully reduced smokeless tobacco consumption through stringent regulations and awareness programs, South Asian nations—including Bangladesh, India, and Pakistan—report alarmingly high prevalence rates, with over 25% of adults using these products. The economic burden of smokeless tobacco-related health issues in Bangladesh is estimated at $1.85 billion annually, further exacerbating public health challenges. This study underscores the urgent need for integrated tobacco control policies that extend beyond physical health to encompass psychological well-being. The stigma surrounding mental health in Bangladesh often leads individuals to use smokeless tobacco as a coping mechanism rather than seeking professional help. Therefore, a multi-sectoral approach—combining stricter regulation, targeted awareness campaigns, and mental health interventions—is imperative to combat both tobacco addiction and its psychological repercussions.